NoSQL: futuro de almacenamiento de datos - Mendoza Jayo, Rubén Gilmar (2015)
The current existence of a behavior or prejudice that indicates that the non-relational model-oriented databases are not competitive compared to the relational model, associated with the lack of interest or lack of education for it professionals on the benefits of NoSQL solutions, and, because, considering that the non-relational model-oriented databases systems just are not in a phase of initiation, they have generated the dilemma that produces is research. The research project seeks to generate a comparative analysis between the relational data model and relational enabling to contribute to a point of view concerning the potential of the NoSQL. This triggered the generation of the proposed migration procedure relational data model to the non-relational and from that reveal the management involved in the development of prototype migration tool based on an experimental architecture outlined in the proposal (RoboSQL) and Finally, benchmarking resulting response time and scalability. The contribution becomes the comparative analysis of data models, which allows a useful reference for translation into relational terminology to non-relational by determining equivalences and differences. This was from the standard properties in data models: structure, constraints and operations. Comparing indicators response time, through a case by case scenarios, reveal that a NoSQL, in most contexts, it is more optimal for their inherent characteristics and performance that has on a given environment. On the side of scalability, evidenced by the variances of data loading and hardware, turned out to be outstanding product NoSQL to their relational counterparts.